2009
DOI: 10.1248/jhs.55.314
|View full text |Cite
|
Sign up to set email alerts
|

Delta-Tocotrienol Causes Decrease of Melanin Content in Mouse Melanoma Cells

Abstract: We examined the effect of δ-tocotrienol on melanin content in mouse melanoma B16 cells. Melanin content was significantly reduced in cells treated with 50 and 100 µM δ-tocotrienol, but not 10 µM δ-tocotrienol. The activity and amount of tyrosinase also significantly decreased in cells treated with 10, 50, and 100 µM δ-tocotrienol. Furthermore, the mRNA level of tyrosinase as measured using realtime PCR was significantly decreased compared to controls in cells treated with 100 µM δ-tocotrienol, but not 10 or 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…13) In the present study, the amount of protein in cells treated with 50 mM d-tocotrienol for 48 or 72 h was similar to that in control cells, however, the amount in cells treated with 100 mM d-tocotrienol for 48 h decreased by 60%, as compared with control values. It was reported that a tocotrienol-rich fraction from palm oil, but not alpha-tocopherol, reduced the viability of activated pancreatic stellate cells by setting up a full death program, independent of cell cycle regulation, and activated pancreatic stellate cells died both through apoptosis, as indicated by increased DNA fragmentation and caspase activation, and through autophagy, as denoted by the formation of autophagic vacuoles and LC3-II accumulation.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…13) In the present study, the amount of protein in cells treated with 50 mM d-tocotrienol for 48 or 72 h was similar to that in control cells, however, the amount in cells treated with 100 mM d-tocotrienol for 48 h decreased by 60%, as compared with control values. It was reported that a tocotrienol-rich fraction from palm oil, but not alpha-tocopherol, reduced the viability of activated pancreatic stellate cells by setting up a full death program, independent of cell cycle regulation, and activated pancreatic stellate cells died both through apoptosis, as indicated by increased DNA fragmentation and caspase activation, and through autophagy, as denoted by the formation of autophagic vacuoles and LC3-II accumulation.…”
Section: Discussionsupporting
confidence: 56%
“…We previously reported that tyrosinase degradation is more important than the decrease of mRNA, as cells treated with 50 mM d-tocotrienol for 24 h was caused the reduction of protein level of tyrosinase, but not mRNA level. 13) From these findings, it was suggested that the degradation of melanosome may be caused by the bulk degradation of transient autophagy induced by d-tocotrienol. The results may be caused by the decrease in melanin synthesis-related enzymes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, these polyphenols have been partially reported to have both antioxidative and anti-melanogenic effects in acerola [28]. As for the antimelanogenic effects of antioxidants, quercetin was shown to inhibit melanin biosynthesis in B16 cells via a decrease in the protein level of tyrosinase [29]. Plausibly, the inhibitory effects of HmHae on the melanogenesis of melan-a cells are attained through the downregulation of MITF and its upstream tyrosinase, TYRP-1 and TYRP-2, by the polyphenolic components.…”
Section: Discussionmentioning
confidence: 99%
“…17) Use of δ-tocotrienol as a therapeutic or preventive drug for hyperpigmentation or as a component of whitening and/or lightening cosmetics, may result in the release of lysosomes or melanosomes from and a decrease in the cholesterol content of cells as side effects.…”
Section: Introductionmentioning
confidence: 99%